2016
DOI: 10.5127/jep.051115
|View full text |Cite
|
Sign up to set email alerts
|

Feature Specific Attention and Return of Fear after Extinction

Abstract: Anxiety disorders are often treated by repeatedly presenting stimuli that are perceptually similar to original stimuli to which fear was originally acquired. Fear can return after it is extinguished because of the differences between these stimuli. It may possible to attenuate return of fear by manipulating attention to the commonalities between feared stimuli and extinction stimuli. After acquiring fear for an animal-like stimulus by pairing with an electro-cutaneous shock, fear was extinguished by repeatedly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 15 publications
1
14
1
Order By: Relevance
“…Finally, that the rate at which SCR extinguished was also not related to return of fear is in contrast to findings from Barry et al () and Barry, Vervliet, and Hermans (in press). However, these studies compared the rate at which US expectancy extinguished with return of expectancy ratings at Test.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Finally, that the rate at which SCR extinguished was also not related to return of fear is in contrast to findings from Barry et al () and Barry, Vervliet, and Hermans (in press). However, these studies compared the rate at which US expectancy extinguished with return of expectancy ratings at Test.…”
Section: Discussioncontrasting
confidence: 93%
“…Regarding expectancy ratings, as described earlier, reduced variability between participants imposed by there only being three possible expectancy responses and the high risk for missing data points could mean that the present sample size was insufficient to reliably observe the expected generalisation and extinction effects. It is less clear why we did not observe the expected SCR effects given that the same design has been used elsewhere (Barry, Vervliet, and Hermans (in press)). As our focus was on individual differences rather than testing a within‐group manipulation, it may be less important that we did not observe these effects.…”
Section: Discussionmentioning
confidence: 83%
“…Interestingly, fear extinction with the original CS protects against return of fear when a GS is tested. Generalization-enhancing interventions may include extinguishing multiple variations of the CS (see Stimulus variability, section 2f(i)), manipulating attention during GS extinction towards common features rather than GS-specific features, and strategies that promote forgetting of specific features of the extinction CS (specific CS memory) [72]. The interaction between context and stimulus changes, which is of greatest clinical relevance, has yet to be investigated.…”
Section: (A) Enhancing Extinction Generalizationmentioning
confidence: 99%
“…The use of non-emotional stimuli allows to isolate potential general attention deficits beyond those observed when individuals face emotional materials (see further below). A few recent studies have focused on how baseline individual differences in attention predict the magnitude or gradient (“speed”) of fear extinction learning ( Waters and Kershaw, 2015 ; Barry et al, 2016a , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The studies by Barry and colleagues ( Barry et al, 2016a , 2017 ) represent a second research tradition that has explored how deficient AC is associated with anxiety vulnerability, and more specifically with cognitive and inhibitory control impairments observed in anxious individuals. In two separate studies in healthy participants, these authors investigated how emotional AC, as measured by self-report ( Barry et al, 2013 ), was associated with fear extinction learning ( Barry et al, 2016a , 2017 ). In the first study, participants were confronted with a perceptually similar stimulus presented after extinction of the original CS, and it was observed that higher emotional AC was associated with faster extinction learning and greater return of fear ( Barry et al, 2016a ).…”
Section: Introductionmentioning
confidence: 99%